Toward a coherent policy on cartel damages - Jens-Uwe Franck; Martin Peitz (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
The focus of cartel damages law is on the recovery of the cartel overcharge. Parties other than purchasers are often neglected, not only as a matter of judicial practice, but also due to legal restrictions. We argue that a narrow concept of standing - which excludes parties that supply either the cartel or the firms that purchase from the cartel with complementary product components - falls short of achieving effective antitrust enforcement and corrective justice in the best possible way. We provide a framework with two complementary products and show that under neither competition nor cartelization do the allocation and the distribution of surpluses depend on the market organization in place. Thus, we argue that prima facie producers of complements should be treated alike, regardless of whether they purchase from the cartel or supply the cartel or the cartel's customers. Moreover, based on various factors that determine the enforcement effect of antitrust damage claims and their role as an instrument to achieve corrective justice, we show that a broad concept of standing is, indeed, the preferable legal solution. While its implementation required a change of the position by the U.S. federal courts, we submit that it would amount to a consistent completion of the legal framework within the EU.
Keywords: 330; cartel damages; antitrust standing; pass-on; suppliers; complementary goods